Rapid Training and Implementation of the Pollock Technique, a Safe, Effective Newborn Circumcision Procedure, in a Low-Resource Setting. (28th May 2015) - Kojima, Noah; Bristow, Claire C.; Pollock, Neil; Crouse, Pierre; Theodore, Harry; Bonhomme, Jerry; Gaston, Claire F. Stéphanie; Dévieux, Jessy G.; Pape, Jean William; Klausner, Jeffrey D.
Male circumcision is highly protective against urinary tract infections, inflammatory conditions of the penis, sexually transmitted infections, and urogenital cancers. We aimed to reintroduce newborn male circumcision through the creation of a training program in Port-au-Prince, Haiti—an area with a considerable burden of preventable urogenital infections, sexually transmitted infections, and low circumcision rate—after an earlier study reported that a majority of Haitian medical providers were in need of and wanted newborn circumcision training. The program was conducted at the GHESKIO Health Centers, a large, non-governmental clinic offering comprehensive pediatric and adult health services. Two Haitian obstetricians and seven nurses learned circumcision procedures. On training completion, one of two obstetricians achieved surgical competence. Introduction of a newborn male circumcision training program was feasible, achieving an acceptable rate of procedural competency and high-quality services. Permanent resources now exist in Haiti to train additional providers to perform newborn male circumcisions.